Mechanical Efficiency at Different Exercise Intensities Among Adolescent Boys With Different Body Fat Levels - Jabbour, Georges; Majed, Lina (Frontiers in Physiology, 2019)
This study investigated the mechanical efficiency (ME) and associated factors in obese, overweight, and normal-weight adolescent boys during incremental cycle exercise test to exhaustion. Forty-five sedentary adolescent boys (13-14 years old) were separated in three groups according to the percentage of fat mass as follows: 15 normal-weight (NW) (body fat: 16.0 ± 1.9%), 15 overweight (OW) (body fat: 24.0 ± 1.6%) and 15 obese (OB) (body fat: 31.0 ± 3.0%). All groups completed an incremental cycle exercise to exhaustion in which energy consumption (E, W), ME (%), lipid oxidation rate (LO, %), plasma epinephrine and norepinephrine concentrations were determined consecutively at rest and at three intensity levels corresponding to 50% and 75% of each participant’s maximal heart rate (50%HRmax and 75%HRmax) and peak oxygen consumption (V ̇O2peak). During the incremental cycle exercise test, plasma epinephrine and norepinephrine responses as well as ME determined at 50%HRmax, 75%HRmax and at VO2peak stages were significantly lower in OB compared to NW and OW individuals (ps < 0.01). Multiple linear regressions showed that body weight (ß = -0.64, p < 0.001), energy consumption (ß = -0.24, p < 0.05) and lipid oxidation (ß = 0.69, p < 0.01) were significant predictors of ME at 50%HRmax. However, at 75%HRmax and V ̇O2peak, significant predictors of ME were epinephrine (ß = 0.34, ß = 0.49, respectively, ps = 0.01), norepinephrine (ß = 0.26, ß = 0.60, respectively, ps < 0.05) and power output (ß = 0.62, ß = 0.71, respectively, ps < 0.01). These findings suggest that excess in body weight exerts a negative effect on ME at a low intensity by increasing energy consumption for obese and overweight adolescent boys, while at higher intensities (75%HRmax and VO2peak) the lower ME could be better explained by the lower power output and catecholamine responses that were attenuated among obese and overweight adolescent boys.